2019
DOI: 10.1007/s40201-019-00388-5
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric ion exchanger supported ferric oxide nanoparticles as adsorbents for toxic metal ions from aqueous solutions and acid mine drainage

Abstract: Background Acid mine drainage (AMD) is a worldwide industrial pollution of grave concern. AMD pollutes both water sources and the environment at large with dissolved toxic metals which are detrimental to human health. This paper reports on the preparation of polymeric ion exchange resins decorated with hydrated iron oxides and their application for the ecological removal of toxic metals ions from AMD. Methods The hydrated iron oxide particles were incorporated within commercial chelating ion exchange resins us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Etale et al (2017) evaluated mesoporous silica nanoparticles and reported that possible configurational advantages of Mn (II) lead to its better adsorption than Cu (II). Similar trends on the influence of pore size were also reported by Nqombolo et al (2019) and Dlamini et al (2019). Table 2 shows the adsorption capacities of some recently studied nano-materials.…”
Section: Nanosorbentssupporting
confidence: 80%
See 1 more Smart Citation
“…Etale et al (2017) evaluated mesoporous silica nanoparticles and reported that possible configurational advantages of Mn (II) lead to its better adsorption than Cu (II). Similar trends on the influence of pore size were also reported by Nqombolo et al (2019) and Dlamini et al (2019). Table 2 shows the adsorption capacities of some recently studied nano-materials.…”
Section: Nanosorbentssupporting
confidence: 80%
“…Adsorption is a versatile technique, in the sense that the adsorbent can be restored and subsequently re-used without reducing the removal efficiency (Bai et al 2017). A range of adsorbents for treatment of AMD have been used, which include high density sludge (Sukati et al 2018;Dlamini et al 2019), alkali-barium-calcium (Mulopo and Motaung 2014;Akinwekomi et al 2017), coal fly ash (Rios et al 2008;Madzivire et al 2019) and lignite (Mohan and Chander 2006;Karagüzel et al 2020). Among the studied adsorbents is activated carbon (Hong et al 2017), silica (Etale et al 2016;Lakovleva and Sillanpää 2013) and ferric oxide (Dlamini et al 2019).…”
Section: Nanosorbentsmentioning
confidence: 99%
“…Polymeric ion exchange resins impregnated with hydrated iron oxide nanoparticles were prepared and tested as an adsorbent for toxic metals removal from AMD (Dlamini, De Kock, Kefeni, Mamba, & Msagati, 2019). The hybrid nanosorbent exhibited higher affinity for toxic metals from AMD.…”
Section: Mine Drainage Remediation Technologymentioning
confidence: 99%
“…At present, there are many treatment methods for AMD, including adsorption (Dlamini et al, 2019), membrane ltration (Ricci et al, 2015), advanced oxidation processes (Munyengabe et al, 2020), and chemical reactions (Kefeni et al, 2017). Nevertheless, these methods are extremely resource intensive with high costs or defective in treating AMD with high concentration of ions, which limits their large-scale application (Shi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%